Incidence and risk factors for surgical site infection after open reduction and internal fixation of intra‐articular fractures of distal femur: A multicentre study. Issue 2 (26th December 2018) - Lu, Kaosheng; Zhang, Jixin; Cheng, Jiaxiang; Liu, Haibo; Yang, Chunyan; Yin, Lichuan; Wang, Hongbing; You, Xiaojun; Qu, Qiaoge
Abstract : There remains a lack of data on the epidemiological characteristics of surgical site infection (SSI) following the open reduction and internal fixation (ORIF) of intra‐articular fractures of distal femur, and the aim of this study was to solve this key clinical issue. The electronic medical records (EMRs) of patients who underwent ORIF for distal femoral fracture from January 2013 to December 2017 were reviewed to identify those who developed a SSI. Then, we conducted univariate Chi‐square analyses and used a multivariate logistic regression analysis model to determine the adjusted risk factors associated with SSI. A total of 724 patients who underwent ORIF of intra‐articular fractures of the distal femur were studied retrospectively, and 29 patients had postoperative SSIs. The overall incidence of SSIs was 4.0% (29/724), with deep SSIs being 1.5% (11/724), and superficial SSIs being 2.5% (18/724). Staphylococcus aureus was the most common causative pathogen (8, 42.1%), followed by mixed bacterial pathogens (5, 26.3%). Open fracture, obesity, smoking, and diabetes mellitus were identified as the adjusted risk factors associated with SSIs. Although modification of these risk factors may be difficult, patients and families should be counselled regarding their increased risk of SSI because these patients potentially benefit from focused perioperative medical optimisation.